Applied relaxation and cortisol secretion: findings from a randomized controlled indicated prevention trial in adults with stress, anxiety, or depressive symptoms. (2nd January 2022) - Kische, Hanna; Zenker, Monique; Pieper, Lars; Beesdo-Baum, Katja; Asselmann, Eva
Abstract: Previous research has shown that relaxation interventions can reduce distress, anxiety, and depression. The exact mechanisms that underlie the efficacy of relaxation interventions remain unresolved. This study aimed to investigate whether applied relaxation (AR) leads to changes in cortisol secretion and whether these effects mediate fewer symptoms due to AR. Data come from a randomized controlled preventive interventional trial ( N = 277) with elevated tension/distress, anxiety, or depressive symptomatology. Participants were randomized to an intervention group (IG; n = 139, received AR training), or a non-interventional control group (CG, n = 138). Psychopathological symptoms were assessed with DASS-21 and diagnoses of mental disorders via DIA-X-5. Cortisol was measured as short-term index in saliva (six times/d for 2 d at pre-, post-, and follow-up [FU] assessment) and long-term index in hair samples (once at pre-assessment and FU, respectively). Data were analyzed as pre-specified secondary analyses of the randomized controlled trial (RCT) on completer basis ( n = 134 CG, n = 102 IG), using multivariable-adjusted linear regression models and mediation analyses (the DASS-21 change in the IG vs. CG with cortisol (area under the curve [AUC]) as mediator). From pre- to post-assessment, total daily salivary cortisol (AUC) decreased more strongly in the IG vs . CG ( β -coefficient: −13.83, 95% confidence interval [CI]: −26.85 to −0.81), but was rendered non-significant when adjusting for pre-assessment AUC. This effect was not found for the cortisol awakening response (CAR) or hair cortisol. There was no evidence for a mediation of cortisol (AUC). These findings provide little support for the idea that cortisol reductions explain the beneficial effects of AR on mental health.